TGACG-BINDING FACTOR 1 (TGA1) and TGA4 regulate salicylic acid and pipecolic acid biosynthesis by modulating the expression of SYSTEMIC ACQUIRED RESISTANCE DEFICIENT 1 (SARD1) and CALMODULIN-BINDING PROTEIN 60g (CBP60g) - Sun, Tongjun (The New phytologist, 2018)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.